2020
DOI: 10.1021/acsami.9b20076
|View full text |Cite
|
Sign up to set email alerts
|

Low Pt-Content Ternary PtNiCu Nanoparticles with Hollow Interiors and Accessible Surfaces as Enhanced Multifunctional Electrocatalysts

Abstract: Developing highly active and durable electrocatalysts with low levels of Pt content toward some crucial reactions including oxygen reduction reaction, hydrogen evolution reaction, and methanol oxidation reaction in an acidic electrolyte environment are desirable but still an open challenge for clean and efficient energy conversion. Herein, we present a facile route to synthesize low Pt-content ternary PtNiCu nanostructures with hollow interior and accessible surfaces (H-PtNiCu-AAT NPs) as enhanced multifunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…EDX analysis was conducted and mentioned in Figure SI 2(b). All three elements (Pt, Ni, and Cu) were found, proposing the successful ternary metal alloy formation as described in literature [24]. Quantitative EDX measurements showed that the average nanomaterial compositional size was about Pt 56 Ni 22 Cu 22 .…”
Section: Characterization Of Ultrasmall Ternary Ptnicu Nanomaterialssupporting
confidence: 73%
See 1 more Smart Citation
“…EDX analysis was conducted and mentioned in Figure SI 2(b). All three elements (Pt, Ni, and Cu) were found, proposing the successful ternary metal alloy formation as described in literature [24]. Quantitative EDX measurements showed that the average nanomaterial compositional size was about Pt 56 Ni 22 Cu 22 .…”
Section: Characterization Of Ultrasmall Ternary Ptnicu Nanomaterialssupporting
confidence: 73%
“…The pure Pt has low binding energy as comparied to Pt 4f of PtNiCu nanomaterial. The electrochemical performance of PtNiCu catalyst was improved due to the change in binding energy cause by the shift of the d‐band center relative to Fermi level, as mentioned previously in litrature [24, 27, 28]. The XPS spectra of PtNi nanomaterial was also analyzed by similar manner and mention in Figure SI 3 having complete spectra of PtNi, with magnified Pt 4 f and Ni 2p spectrum.…”
Section: Resultsmentioning
confidence: 63%
“…[2] However, the low specific activity and poor long-term durability of platinum have not yet reached the requirements for commercial application of proton exchange membrane fuel cells and metal-air batteries. [3] Alloying of Pt with other transition metals is a smart strategy to remarkably enhance the catalytic performances, raised by electronic ligand and ensemble So, it is also very suitable for preparing alloys in a large scale and controlling morphologies of alloys, such as PtRuCu nanoboxes, [13] hollow PtNiCu nanoparticles, [14] and PtPdRuTe nanotubes. [15] Chen and co-workers [13] fabricated hollow and porous PtRuCu cubic structures through galvanic replacement with Cu 2 O nanocubes as templates and K 2 PtCl 4 together with RuCl 3 as metal sources.…”
Section: Introductionmentioning
confidence: 99%
“…This special morphology effectively improves atom utilization and electron transfer, giving it excellent electrocatalytic performance. The Lin group [14] presented a facile route to synthesize low-Pt-content ternary PtNiCu nanostructures with hollow interior and accessible surfaces. Zhou and co-workers [16] synthesized the CoAuPd alloy with metallic Co as a self-sacrifice template by galvanic replacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation